Post-marketing safety surveillance of erenumab: new insight from Eudravigilance. Issue 9 (2nd September 2022) - Liang, David; Sessa, Maurizio
ABSTRACT: Background: We aimed at evaluating adverse drug reactions during the post-marketing phase with erenumab as the suspected/interacting drug in Eudravigilance, with the final goal of investigating the consistency of the disproportionality signals (DS) for erenumab in Eudravigilance and the American Food and Drug Administration Adverse Event Reporting System (FDA FAERS) and undetected DS from Eudravigilance. Research design and methods: Eudravigilance was screened in the period from October 2019 to October 2020. Disproportionality measure was performed using the Reporting Odds Ratio (ROR) according to the guidelines by the European Medicine Agency and using sumatriptan as the control group. Results: 3381 cases were reported in the study period. Forty DS were identified both in Eudravigilance and FAERS. Sixteen DS were not identified in FAERS, 10 DS were found to have biological probability and six DS were considered false-positive and potentially related to confounding by indication. The three system organ classes with the highest proportion of adverse events were general disorders and administration site conditions (16.12%), nervous system disorders (15.95%), and gastrointestinal disorders (13.59%). Conclusions: Adverse events reports were mostly reported as non-serious. Co-analysis of multiple spontaneous reported databases unveiled undetected DS for erenumab in individual databases. Future studies should be conducted to confirm the associations and potential clinical implications.